SMART LIVING TECHNOLOGY DALAM KUALITAS KESEHATAN: STUDI KASUS JA-KI - Gradus Amsianus Dungkal Ropan; Divio Muhamad Julian; Oliver Berkah Hulu; Ivan Darwawan (Triwikrama: Jurnal Ilmu Sosial, 2024)
Advances in digital technology have had a significant impact on the health sector, especially in big cities such as Jakarta. One of the innovations developed by the DKI Jakarta Provincial Government is the JAKI (Jakarta Kini) application, a super app that offers a variety of digital health services. This study aims to evaluate the application of JAKI in the context of Smart Living Technology (SLT), with a focus on accessibility, service effectiveness, and its impact on public health awareness. Qualitative research methods with case studies are used to collect data through in-depth interviews, user satisfaction surveys, and analysis of annual reports. The results of the study show that JAKI has succeeded in improving the efficiency of health services, such as online queues and mental health consultations, as well as increasing public awareness about disease prevention. Despite the challenges related to digital literacy and demographic data collection, this application shows great potential to support Jakarta's public health in a more efficient and inclusive manner. JAKI can be a model for the implementation of digital health technology in other cities, with further development in the healthcare sector.